An investigation into linguistic features of names of food and drinks in restaurant menus in Hoi An acient town in Vietnamese and English - Nguyễn Thị Mỹ Duyên (The University of Da Nang, 2012)
Introduction; Literature review and theoretical background; Method and procedure...